Cold start for the green innovation machine - Philippe Aghion; Reinhilde Veugelers; Clément Serre (Bruegel, 2009)
This Policy Contribution accompanies the Policy Brief, 'No Green Growth Without Innovation'. Written by Senior Non-Resident Fellow Philippe Aghion, Senior Resident Fellow Reinhilde Veugelers and Researcher Clément Serre, this paper discusses the state of green innovation and goes into more depth in discussing the current problems in the area. Examining research and development, patent, and venture capital data, the authors point out that there is momentum for private investment in green technologies. However, they argue that, thus far, the implicit tax rate on energy in the EU27 is too low and fragmented, the carbon price in the EU Emissions Trading System is too volatile, and the public R&D expenditures dedicated to energy and environment are too low. They conclude that immediate state intervention is necessary, at least at the onset, to ensure that the 'green innovation machine' gets properly started.
Keywords: 330; Klimaschutz; Umwelttechnik; Forschungssubvention; Forschungs- und Technologiepolitik; EU-Staaten